2016
DOI: 10.1071/py15032
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the views and experiences of women living in the city centre of Manisa, Turkey, regarding domestic violence

Abstract: Domestic violence against women is an important social and public health problem worldwide resulting from unequal power relationships between men and women. The purpose of the present cross-sectional descriptive study was to determine the factors affecting the views and experiences of women living in the city centre of Manisa, Turkey, regarding domestic violence. The data were collected from a representative sample of women (n=873) in 2012. The socio-demographic questionnaire and the World Health Organization'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…The rate of economic violence is 23% according to the İlknur et al (2014). In Turkey, exposure to economic violence rates among women varies between 23% and 25% (Alkan et al, 2020; Duva, 2019; Güçlü & Cann, 2018; Özpınar, 2018a, 2018b, 2020; Özpınar et al, 2016; İlknur et al, 2014). The research results comply with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of economic violence is 23% according to the İlknur et al (2014). In Turkey, exposure to economic violence rates among women varies between 23% and 25% (Alkan et al, 2020; Duva, 2019; Güçlü & Cann, 2018; Özpınar, 2018a, 2018b, 2020; Özpınar et al, 2016; İlknur et al, 2014). The research results comply with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…were exposed to economic violence in the last 12 months [45], in another study conducted in Manisa 7.4% of women [9] and again in another study conducted in the Manisa city center, 24.4% of women were exposed to economic violence [46]. It was found in a study conducted in Konya, that 13.5% of married women were exposed to sexual and economic violence [14]; in another study conducted in Turkey's capital Ankara showed that 60.4% of women [28] and 19.3% of the women in Edirne, were exposed to economic violence [47].…”
Section: Plos Onementioning
confidence: 99%
“…Domestic violence against women is a major social problem arising from unequal power relationships between men and women [45]. Turkish society has a traditional, patriarchal structure in which the culture has different hierarchies and different areas of activity for men and women [50].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations